Software, Animation and the Moving Image - Wood, A. author. aut Link
VIII, 127 p.
Keywords: Software, Animation and the Moving Image brings a unique perspective to the study of computer-generated animation by placing interviews undertaken with animators alongside an analysis of the user interface of animation software. Wood develops a novel framework for considering computer-generated images found in visual effects and animations.